The Relationship of Information, Motivation And Behavioral Skill (IMB Model) Based Health Behavior to Tuberculosis Medication Compliance in Tuberculosis Patients at Putri Ayu Health Center - Sari, Putri Puspita; Rudini, Dini; Martawinarti, RTS Netisa; Sari, Putri Irwanti; Sulistiawan, Andika (Jurnal Pinang Masak, 2025)
Background: Tuberculosis (TB) is still a global health problem with a high incidence rate, including in Indonesia. The success of therapy is highly dependent on the patient's adherence to treatment. The Information, Motivation, and Behavioral Skills (IMB) model describes compliance through three main components, namely information, motivation, and behavioral skills. Objective: To determine the relationship between health behavior based on the IMB Model and medication adherence in tuberculosis patients at the Putri Ayu Health Center, Jambi City. Methods: This study used a cross-sectional design with a quantitative approach. The sampling technique is a total sampling with a total of 48 respondents. The research instruments were in the form of IMB Model questionnaires and medication adherence. Data analysis using Gamma tests. Results: There was a significant association between personal motivation (p=0.001), social motivation (p=0.001), and behavioral skills (p=0.001) with medication adherence, whereas the information showed no significant association (p=0.639). Conclusions: IMB Model-based health behaviors have a meaningful relationship with medication adherence in tuberculosis patients. Keywords: Tuberculosis, Medication Adherence, Information Motivation Behavioral Skills (IMB) Model